GAMBARAN KADAR KALSIUM DARAH PADA WANITA MENOPAUSE DI BANJAR BINOH KAJA, DESA UBUNG KAJA, KECAMATAN DENPASAR UTARA - IGA Dewi Sarihati (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2016)
ABSTRACT Background: Menopause women are one of the groups that have a high risk of osteoporosis, because at that time the amount of estrogen is reduced so that the absorption of calcium from the digestive tract will be reduced about 20-25%. This is the reason why the level of calcium decreasing in blood. According to the initial observation at Banjar Binoh Kaja by researcher, from 10 menopause women, four of them are at risk of osteoporosis. Methode: This study is a descriptive study which describes the blood calcium levels in menopause women at Banjar Binoh Kaja, Ubung Kaja Village, North Denpasar District, by doing measurement on their blood calcium concentration with O – Cresolphthalein Complexon (OCPC) method. The 34 respondents taken from total population of menopause women in age range 50-65 years. Respondent was selected using purposive sampling with criteria: menopause women in age range 50-65 years and not undergoing hormone replacement therapy. .Result: The results showed that the average concentration of blood calcium is 8,83 mg/dL which 11.76% respondents had low levels of blood calcium and 88.24% respondents had normal blood calcium levels. 33,33% respondents in age range 62 – 65 years and 66,67% respondents in 16 – 20 years periods of menopause has decrement of blood calcium levels. Coclusion: The decrement of blood calcium levels mostly held in respondents in age range 62 – 65 years and respondents with 16-20 years periods of menopause. Keywords: blood calcium, menopause